Reply to Vogt's comments on the paper "Fibrous-clay mineral formation and soil evolution in Aridisols of northeastern Patagonia, Argentina" by P.J. Bouza, M. Simón, J. Aguilar, H. del Valle and M. Rostagno - Bouza, Pablo Jose (2009)
Vogt's comments emphasize the potential influence that the cryogenic processes could have had on the genesis of the soils analyzed in this study. We really appreciate her comments. Indeed, we took into consideration and cited one of her studies dealing with cryogenic processes and sepiolite formation. However, our results led us to conclusions different to the ones held by Vogt.